How to write and publish a scientific paper - Day, Robert A. 1924-; Gastel, Barbara (Greenwood, 2011)
"This newly updated version of the classic guide to writing and publishing scientific papers provides the tools needed to succeed in the communication aspects of a scientific career"--Provided by publisher